2017
DOI: 10.1111/resp.13132
|View full text |Cite
|
Sign up to set email alerts
|

Community‐acquired pneumonia management and outcomes in the era of health information technology

Abstract: Pneumonia continues to be a leading cause of hospitalization and mortality. Implementation of health information technology (HIT) can lead to cost savings and improved care. In this review, we examine the literature on the use of HIT in the management of community-acquired pneumonia. We also discuss barriers to adoption of technology in managing pneumonia, the reliability and quality of electronic health data in pneumonia research, how technology has assisted pneumonia diagnosis and outcomes research. The goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…As pneumonia remains a leading cause of morbidity and mortality, several have postulated whether using HIT in this population could improve clinician adherence with recent guidelines as well as improve patient outcomes. Mecham et al . published a recent review examining HIT in the management of CAP.…”
Section: Respiratory Infectionsmentioning
confidence: 98%
See 1 more Smart Citation
“…As pneumonia remains a leading cause of morbidity and mortality, several have postulated whether using HIT in this population could improve clinician adherence with recent guidelines as well as improve patient outcomes. Mecham et al . published a recent review examining HIT in the management of CAP.…”
Section: Respiratory Infectionsmentioning
confidence: 98%
“…As pneumonia remains a leading cause of morbidity and mortality, several have postulated whether using HIT in this population could improve clinician adherence with recent guidelines as well as improve patient outcomes. Mecham et al 54 published a recent review examining HIT in the management of CAP. Studies showed that interventions such as, automated pharmacy technology, computerized clinical decision support (CCDS) and computerized physician order entry (CPOE) improved guideline and CMS core measure adherence, though results have been inconsistent across studies.…”
Section: On the Horizonmentioning
confidence: 99%
“…We all hope that the optimism of Finch et al . and Mecham et al . will be realized and help us meet the challenge of what nature will come up with over the coming decades.…”
mentioning
confidence: 93%
“…Hadfield and Bennett argued that there is now a well‐defined bundle of care associated with best patient outcomes that includes rapid, guideline‐concordant antibiotics, probably the combination of a beta‐lactam and a macrolide, early treatment of co‐morbidities including glucose and electrolyte stabilization, adequate venous thromboprophylaxis and early mobilization. Mecham et al . explored the increasing use of technology to improve patient outcomes, especially clinical decision support tools.…”
mentioning
confidence: 99%
“…[ 21 – 22 ] Although comprehensive measures can achieve a certain effectiveness, there are still many difficulties in the treatment of the disease due to the emergence of insulin resistance and drug-resistant bacteria. [ 11 , 23 ] Such as the repeated use of broad-spectrum antibiotics can easily induce flora imbalance and mutation strains. What is more, even if blood sugar and inflammation are controlled, there is still no significant improvement in the patient's condition.…”
Section: Introductionmentioning
confidence: 99%